2015
DOI: 10.1111/pme.12602
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Prescription Opioid Monitoring Guidelines among Residents and Attending Physicians in the Primary Care Setting

Abstract: Objective To compare adherence to opioid prescribing guidelines and potential opioid misuse in patients of resident versus attending physicians. Design Retrospective cross-sectional study. Setting Large primary care practice at a safety-net hospital in New England. Subjects Patients 18–89 years old, with at least one visit to the primary care clinic within the past year and were prescribed long-term opioid treatment for chronic non-cancer pain. Methods Data were abstracted from the EMR by a trained dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…(1) Efforts to manage this increase in mortality have focused on modifying the prescribing practices of providers. (2) Mandated urine testing, pain agreements, and inspections of prescription drug monitoring program data have become standard practice, yet there are few data to support a link between such interventions and reduced opioid-related morbidity or mortality. In fact, while opioid analgesic deaths have recently plateaued, heroin use and overdose deaths have skyrocketed, suggesting possible unintended consequences of opioid stewardship initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Efforts to manage this increase in mortality have focused on modifying the prescribing practices of providers. (2) Mandated urine testing, pain agreements, and inspections of prescription drug monitoring program data have become standard practice, yet there are few data to support a link between such interventions and reduced opioid-related morbidity or mortality. In fact, while opioid analgesic deaths have recently plateaued, heroin use and overdose deaths have skyrocketed, suggesting possible unintended consequences of opioid stewardship initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with studies that found low adherence rates for urine toxicology tests among clinicians who cared for patients at increased risk of misuse 20,3840 and in safety net health settings. 41 …”
Section: Discussionmentioning
confidence: 99%
“…28 Similarly, only one patient between both groups had any documentation that a urine drug screen was utilized, consistent with prior work that providers infrequently order urine drug screens, though more recent studies show this may be improving. 9, 10, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Little is known about how providers make decisions about opioid dosing (i.e., to continue, increase, or decrease a patient’s dose) when they write individual prescriptions. Prior studies examining risk factors for high-dose opioid use and opioid misuse have found that documentation of guideline-concordant practices for safe opioid prescribing is poor; 9, 10, 11, 12, 13 however, neither providers’ rationale for individual opioid prescriptions nor encounter-level factors associated with opioid dose increases have been previously studied.…”
Section: Introductionmentioning
confidence: 99%